Boda-bodas Rule: Non-agricultural Activities and Their Inequality Implications in Western Kenya - Jann Lay; George Michuki M'Mukaria; Toman Omar Mahmoud (German Institute of Global and Area Studies (GIGA), 2007)
Engagement in non-agricultural activities in rural areas can be classified into survival-led or opportunity-led. Survival-led diversification would decrease inequality by increasing the incomes of poorer households and thus reduce poverty. By contrast, opportunity-led diversification would increase inequality and have a minor effect on poverty, as it tends to be confined to non-poor households. Using data from Western Kenya, we confirm the existence of the differently motivated diversification strategies. Yet, the poverty and inequality implications differ somewhat from our expectations. Our findings indicate that in addition to asset constraints, rural households also face limited or relatively risky high-return opportunities outside agriculture. – – Die Aufnahme von Tätigkeiten außerhalb der Landwirtschaft kann in ländlichen Gebieten sowohl durch die Notwendigkeit zu überleben motiviert sein als auch durch das Vorhandensein günstiger Gelegenheiten. Diversifizierung aufgrund des Überlebensmotivs verringert Ungleichheit, da das Einkommen ärmerer Haushalte wächst und somit die Armut sinkt. Diversifizierung aufgrund des Gelegenheitsmotivs steigert hingegen Ungleichheit und hat nur geringe Auswirkung auf die Armut, da sie sich für gewöhnlich auf nichtarme Haushalte beschränkt. Anhand von Daten aus Westkenia bestätigen wir die Existenz der unterschiedlich motivierten Diversifizierungsstrategien. Die Auswirkungen auf Armut und Verteilung entsprechen jedoch nur teilweise unseren Erwartungen. Unsere Ergebnisse zeigen, dass Haushalte in ländlichen Gebieten neben Kapitalbeschränkungen begrenzte oder relativ riskante profitable Möglichkeiten außerhalb der Landwirtschaft haben, Katalysator für den Zerfall des seit Jahrzehnten etablierten Zweiparteiensystems des Landes.
Keywords: Q12; O17; I31; 330; income diversification; non-agricultural activities; inequality; poverty; sub-Saharan Africa; Kenya; Dorfwirtschaft; Landwirtschaftlicher Kleinbetrieb; Diversifikation; Ländliches Einkommen; Einkommensverteilung; Kenia (West); Afrika südlich der Sahara